THE PREPARATION FEATURES OF HIGH-QUALITY PRESENTATIONS IN POWERPOINT (Socio-economic relations in the digital society, 2019)
The ownership of reliable information is critical for making the right decision. To convince the audience to convey the opinion, point of view, it is necessary to use multiple channels of perception audience. Simply to use auditory and visual channels. Th e most accurate, visual and auditory simultaneously way to convey information to consumers in a presentation is the soft ware of Microsoft Offi ce PowerPoint. The high-quality presentation is created with the peculiarities of perception audience. The study clarified the principles and rules of good (most trustworthy and complete) submission of information by the soft ware PowerPoint. In order, there are clarifi ed the features of the typical audience of perception, investigated the transfer of information from sources (speaker) to its customers; found criteria that must be followed by the presentation and formulated recommendations for the assembly of high-performance presentation.
Keywords: рresentation; transmitting information; effectiveness; software